Rwanda district agricultural officers use national climate services to match seed to local conditions for 88,000 farmers and provide supplemental irrigation water - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
District agronomists, trained to understand Meteo Rwanda’s online Maprooms, are using climate information to improve their services to farmers. In the Western highlands, agronomists used climate information to match crop varieties to local conditions, providing more suitable hybrid maize seeds to 87,872 farmers. Using crop water deficit calculations based on climate information, Bugesera District authorities provided supplemental irrigation water, pumped from a lake into a lined reservoir, to enable 188 farmers with supplemental irrigation to cope with prolonged dry spells.